(untitled) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2023)
Religious moderation is one way to deal with diversity today. The word moderation comes from the Arabic word al-wasathiyah. The practice of Islamic moderation in Dungus Village is manifested harmoniously in Islamic religious activities such as routine recitation, celebration of Islamic days, and Islamic organizational activities. The purpose of writing this article is to show how the implementation of religious moderation with different tendencies is still applied today and how religious moderation can be strengthened in the midst of differences in Islamic religious perspectives. The method used in this research is field study. This type of research is qualitative research where the material produced is presented clearly, coherently, and narratively from various points of view. This research was conducted during the KKN period, from 07/05/2023 to 18/08/2023 in Dungus Village, Kunjang District, Kediri Regency. The results showed that through religious education activities at TPQ, it became a forum for spreading national ideas, introducing multicultural values, bringing religious messages in a peaceful manner and spreading love for humanity. Religious moderation through religious activities also runs well and harmoniously in the Dungus Village community without any conflict between Islamic organizations. This activity has a positive impact on increasing residents’ knowledge of Islamic religious activities, uniting various Islamic religious organizations in various activities, improving and creating harmony between Muslims.